Marketing IQOS in a dark market. Issue 2 (3rd May 2018) - Mathers, Annalise; Schwartz, Robert; O'Connor, Shawn; Fung, Michael; Diemert, Lori
Abstract : Introduction: Phillip Morris International (PMI) is pushing hard to promote IQOS heat-not-burn cigarettes in Ontario, Canada. Canada regulates IQOS as a tobacco product so that the robust tobacco marketing ban creates challenges to its promotion. Methods: We collected data on IQOS promotion in 49 retail outlets, and through interviews with clerks and observations outside an IQOS store. Results: The dominant marketing channel is the visible availability of IQOS in a large number of tobacco retail outlets—1029 across Ontario. Several stores display the price of 'heated tobacco' on one of three price signs which are permitted despite Ontario's total display ban. IQOS boutique stores are the locus of aggressive promotion including exchanging a pack of cigarettes or lighter for an IQOS device, launch parties, 'meet and greet' lunches and after-hour events. Outside the store, promotion includes a prominent IQOS sign, a sandwich board sign reading 'Building a Smoke-Free Future' and sales representatives regularly smoking IQOS. Membership services: Upon acquiring an IQOS device one can register to access the IQOS website store5 and receive customer support services, a map of retail locations and a product catalogue. Members receive regular email invitations to complete surveys with opportunities to win prizes. Conclusions: These promotion activities have undoubtedly made substantial numbers of Ontarians aware of IQOS. Yet, the government has not provided guidance as to absolute and relative potential harms. Our observations of tactics to promote a new tobacco product in a dark market may inform government regulatory policy and non-governmental organisation efforts wherever heat-not-burn products are introduced.